Ethical reasoning in clinical education - Quail, Michelle; Sanderson, Brooke; Leitão, Suze (Speech Pathology Australia, 2013)
Ethical reasoning within the context of clinical education is explored using the casuistry approach to ethical decision-making through the layers of the Seedhouse ethical grid (a decision-making tool). The casuistry approach guides clinicians’ actions by encouraging them to map previous experiences onto the profession’s underlying principles in order to help them proactively plan for future clinical education experiences. In this paper, we present a model which highlights the unique and delicate balance between the multiple stakeholders involved in clinical education, and the shift in responsibilities and relationships that can occur. The need to understand ethical decision-making processes, be proactive with ethical thinking, and ensure clarity in expectations is discussed. A framework is proposed to assist clinical educators in finding the balance between their ethical obligations to their students, their clients and themselves.